Static microsimulation research on citizen's basic income for the UK: A personal summary and further reflections - Malcolm Torry (University of Essex, Institute for Social and Economic Research (ISER), 2019)
A Citizen's Basic Income, sometimes called a Basic Income, a Universal Basic Income, or a Citizen's Income, is an unconditional and nonwithdrawable income paid to every individual. The purpose of this paper is to summarise the results of microsimulation research on Citizen's Basic Income schemes undertaken by this author during the past fifteen years; to update recent research; and to reflect on the journey taken by that research. The paper explores the ways in which the contemporary policy context and constructive criticism of previous research projects have resulted in changes to the methods employed, discusses ways in which the research has influenced the policy process, and draws comparisons with the work of other microsimulation researchers. The increasingly lively debate on Citizen's Basic Income has generated a wide variety of questions relating to Citizen's Basic Income's feasibility, and the penultimate section of this paper addresses some of the most pressing of those questions. A final section draws lessons from the research journey recounted in this paper, and suggests avenues for future research activity.
Keywords: C80; H53; H55; I38; R20; 330; Citizen's Basic Income; microsimulation